STATEMENT OF WILLIAM E. ALLI CHAIRMAN, HEALTH & SAFETY COMMITTEE, LOCAL 1534 AMERICAN FEDERATION OF GOVERNMENT EMPLOYEES BEFORE THE SUBCOMMITTEE ON HEALTH AND THE ENVIRONMENT HOUSE ENERGY AND COMMERCE COMMITTEE 850612 - ALLI,WE (Tufts Archival Research Center, 2007)
Statement of William E Alli of the American Federation of Government Employees before the Subcommittee on Health and the Environment, House Energy and Commerce Committee. Testifies in favor of the Non-Smokers Protection Act of 1986. Asserts that the majority of federal workers want smoking restrictions. Discusses experiences with new regulations and modifications needed in the bill. Includes summary of results from a survey of smoking in the workplace.